2004
DOI: 10.1002/mrd.20212
|View full text |Cite
|
Sign up to set email alerts
|

Mouse embryonic stem cells and preimplantation embryos require signaling through the phosphatidylinositol 3‐kinase pathway to suppress apoptosis

Abstract: Whereas most mammalian cells require extracellular signals to suppress apoptosis, preimplantation embryos can survive and develop to the blastocyst stage in defined medium without added serum or growth factors. Since cells of these embryos are capable of undergoing apoptosis, it has been suggested that their lack of dependence upon exogenous growth factors results from the production of endogenous growth factors that suppress apoptosis by an autocrine signaling mechanism. In the present study, we have examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…Previously we and others demonstrated that the PI3K pathway is present and functional during murine preimplantation development (32,34,35,42); however, there is still relatively little data regarding the physiologic ramifications of inhibiting this pathway in preimplantation embryos. Because of the connection between the PI3K signal transduction pathway, growth factors, and cell survival in other systems (18,43), we first investigated whether inhibition of PI3K results in the induction of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we and others demonstrated that the PI3K pathway is present and functional during murine preimplantation development (32,34,35,42); however, there is still relatively little data regarding the physiologic ramifications of inhibiting this pathway in preimplantation embryos. Because of the connection between the PI3K signal transduction pathway, growth factors, and cell survival in other systems (18,43), we first investigated whether inhibition of PI3K results in the induction of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…There is a deficit in the number of homozygous knock-out embryos detected at E3.5 (blastocyst stage) implying that this protein is important during early development. In addition, studies have shown that the inhibition of PI3K leads to decreased numbers of embryos that develop to the morula and blastocyst stage when cultured in vitro and to the induction of apoptosis during this developmental period (34,35).…”
mentioning
confidence: 99%
“…Also, several studies reported that IGF-I promotes pre-implantation embryo development and cell numbers in many species, including mouse [15], cow [18], and human [17]. The antiapoptotic effects of IGF-I generally act through a phosphatidylinositol 3-kinase (PI3K)/Akt signal pathway which subsequently inactivates pro-apoptotic proteins such as Bad and caspase-9 and stimulates anti-apoptotic proteins, including Bcl-2, a number of transcription factors and translational regulatory proteins [41,42]. Therefore, IGF-I may promote embryonic development by an anti-apoptotic effect instead of increasing HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%
“…In Experiment, 2 the effect of LY294002 [27], an inhibitor of PI3K-a second messenger present in the mouse preimplantation embryo involved in the maintenance of pluripotency [25,28]-was examined in the presence or absence of insulin to determine whether insulin was acting via PI3K. Since the PI3K second messenger pathway involves the subsequent phosphorylation and inactivation of GSK3 [29], which has been shown to be beneficial for maintaining cells in a pluripotent state in outgrown ICMs [30], we hypothesized that the activation of GSK3 would inhibit the positive response of insulin, while inactivation would mimic the effects of insulin.…”
Section: Experimental Designmentioning
confidence: 99%